2023
DOI: 10.1164/rccm.202206-1230oc
|View full text |Cite
|
Sign up to set email alerts
|

Low CC16 mRNA Expression Levels in Bronchial Epithelial Cells Are Associated with Asthma Severity

Abstract: Rationale: CC16 is a protein mainly produced by nonciliated bronchial epithelial cells (BECs) that participates in host defense. Reduced CC16 protein concentrations in BAL and serum are associated with asthma susceptibility.Objectives: Few studies have investigated the relationship between CC16 and asthma progression, and none has focused on BECs. In this study, we sought to determine if CC16 mRNA expression levels in BECs are associated with asthma severity.Methods: Association analyses between CC16 mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Decreased CC16 serum levels are rather characteristic in chronic lung diseases with high degrees of bronchial epithelial cell damage, as it was recently shown by Li et al. who demonstrated an association of CC16 mRNA expression levels and asthma susceptibility, severity and exacerbations ( 13 ).…”
Section: Discussionmentioning
confidence: 77%
“…Decreased CC16 serum levels are rather characteristic in chronic lung diseases with high degrees of bronchial epithelial cell damage, as it was recently shown by Li et al. who demonstrated an association of CC16 mRNA expression levels and asthma susceptibility, severity and exacerbations ( 13 ).…”
Section: Discussionmentioning
confidence: 77%
“…Low CC16 mRNA expression in bronchial epithelial cells was reported to involve in asthma susceptibility and severity. 28 The lower levels of serum CC16 were reported in those with COPD-asthma overlap having a positive BDR. 11 Allergen exposure-induced free eosinophil granules (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…CC16 is a pneumoprotein secreted from terminal respiratory bronchioles in humans. Low CC16 mRNA expression in bronchial epithelial cells was reported to involve in asthma susceptibility and severity 28 . The lower levels of serum CC16 were reported in those with COPD‐asthma overlap having a positive BDR 11 .…”
Section: Discussionmentioning
confidence: 99%
“…found that CC16 mRNA expression levels were negatively correlated with expression levels of Th2 genes, and CC16 could decrease sputum eosinophils through downregulating IL-5 and IL1RL1. 61 Though these findings were found in allergic respiratory diseases like asthma and ECRS, it provided possible explanation biologically for the link between CC16 and eosinophilic COPD.…”
Section: Discussionmentioning
confidence: 95%